MENGELOMPOKKAN REMAJA BERDASARKAN NILAI IMT (INDEX MASA TUBUH) MENGGUNAKAN ALGORITMA K - MEANS - Pratiwi, Elsa (FORMAT, 2024)
According to the Indonesian Minister of Health in 2010, the age limit for adolescents is between 10 to 19 years old and unmarried. Meanwhile, according to BKKBN, the age limit for adolescents is 10 – 21 years old (Ministry of Health, 2010). [1]. The purpose of the study is to produce a grouping of BMI values in adolescent posyandu in the UPTD Pengaringan Health Center and adolescent posyandu in the UPTD Pengaringan Health Center. Based on observations to the research places of the UPTD Pengaringan Inpatient Health Center and the Youth Posyandu in the area of the UPTD Pengaringan Inpatient Health Center. Where to determine BMI is still calculated by excel and the data has not been neatly arranged. So that it is not possible to accurately measure the grouping of body mass status in adolescents, to group the BMI (Body Mass Index) of adolescents still have to search and recalculate the data according to needs, this takes a long time and risks inaccuracy. This research uses the K-means algorithm, the classification method using data mining and for testing using ...Keywoard: IMT, K – means, Data mining, Rafid minner, Google colab